Answer:
Step-by-step explanation:
\[2~ sin^2 x+3sin x+1=0\]
\[2sin^2x+2sin x+sin x+1=0\]
2sinx(sin x+1)+1(sin x+1)=0
(sin x+1)(2 sin x+1)=0
either sin x+1=0
sin x=-1=sin 3π/2=sin (2nπ+3π/2)
x=2nπ+3π/2,where n is an integer.
or 2sin x+1=0
sin x=-1/2=-sin π/6=sin (π+π/6),sin (2π-π/6)=sin (2nπ+7π/6),sin (2nπ+11π/6)
x=2nπ+7π/6,2nπ+11π/6,
where n is an integer.
Answer:
5/16 of a yard per pillow
Step-by-step explanation:
1. Divide 5/8 by 2 (or 2/1)
2. 5/8 * 1/2 (following the division of fraction models of 'keep, change, flip'
5*1 = 5 and 8 * 2 = 16 5/16
Answer:
y= 4x-9
Step-by-step explanation:
Answer:
ahsbdbsbevdjsbebdbdhdbdhdbd